2022
DOI: 10.1021/acs.orglett.2c00858
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Highly Selective Hydrosilylation of Silyl or Boryl Alkene: A Method for Preparing Chiral Geminated Disilyl and Borylsilyl Reagents

Abstract: The copper-catalyzed highly selective hydrosilylation of silyl or boryl alkene has been developed. This chemistry could afford a practical method for preparing chiral geminated disilyl and borylsilyl reagents, which are useful organosilanes and versatile synthons for organic synthesis. The experimental data suggested that this reaction could be compatible with a variety of functional groups. Furthermore, the utility of the gem-dimetal compounds, which could be prepared by this chemistry, has been well illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Recently, due to their abundance, complex catalysts made from base metals, particularly first row transition metals, have been actively studied as alternatives to Pt-complex catalysts. 4,5 Since their success in the early 2010s, 3,6,7 many first row transition metal-complex catalysts, such as Mn, 5,8 Fe, 3,7,9–14 Co, 10,11,15,16 Ni, 17 and Cu complexes, 18,19 have been used in the hydrosilylation of alkenes (olefins), alkynes, ketones, and other similar compounds. The improvement of first row transition metal-complex catalysts has achieved high turnover numbers as well as high regio- and stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, due to their abundance, complex catalysts made from base metals, particularly first row transition metals, have been actively studied as alternatives to Pt-complex catalysts. 4,5 Since their success in the early 2010s, 3,6,7 many first row transition metal-complex catalysts, such as Mn, 5,8 Fe, 3,7,9–14 Co, 10,11,15,16 Ni, 17 and Cu complexes, 18,19 have been used in the hydrosilylation of alkenes (olefins), alkynes, ketones, and other similar compounds. The improvement of first row transition metal-complex catalysts has achieved high turnover numbers as well as high regio- and stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, transition-metal catalyzed methods for borosilane synthesis are generally limited to one type of silanes (e.g. secondary silanes) [7][8][9][10][11][12][13][14] . It was found that primary, secondary and tertiary silanes were all competent substrates in our transformation, delivering structurally diverse geminal borosilanes effectively (47)(48)(49)(50)(51)(52).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of borosilanes, mainly through transition-metal catalysis, has attracted much attention in the last decade (Fig. 1a) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . For instance, Morken and co-workers reported the synthesis of geminal borosilanes through Pt-catalyzed hydrosilylation of β-alkyl-substituted alkenyl boronates 8 .…”
Section: Introductionmentioning
confidence: 99%
“…10–12 Due to reactivity and selectivity issues with hydrosilylation of vinylsilanes, access to gem -bis(silanes) through double hydrosilylation of alkynes is a challenge, and at first, such processes were observed only as side reactions. 13 However, several research groups have recently reported successful double hydrosilylation of alkynes leading to gem -bis(silanes) (Scheme 1). Zhu's team utilised an iron( ii ) complex with a phenanthroline derived ligand that catalysed double anti -Markovnikov hydrosilylation of terminal aliphatic alkynes (Scheme 1a).…”
mentioning
confidence: 99%